Cypriote Bronze Age Pottery Found in Egypt - Merrillees, R. S.
Ph.D.; Supervisor: W. B. Emery; espec. Chapter III, where “in conclusion, an attempt is made to relate the growth fluctuations and decline of Cypriote and Syrian trade with Egypt to the contemporary political events in the Levant. Since Ras Shamra, to judge by its geographical situation and material remains, was the pivot on which Cypriote commerce with Egypt revolves, the history of that site is given particular prominence in the survey. Drawing on literary as well as archaeological information, it emerges that the intensity of commercial intercourse between Cyprus and Egypt varied in proportion to the degree of autonomy Ras Shamra enjoyed . . ..”.